International Conference “Interfaces between Legality and Illegality in Markets” - Zoya Kotelnikova (Journal of Economic Sociology, 2015)
The conference “Interfaces between Legality and Illegality in Markets” was held on February, 5–6, 2015 at The Max Planck Institute for the Study of Societies in Cologne. Organized by Prof. Jens Beckert (Director at the Max Planck Institute for the Study of Societies) and Matías Dewey (Research Fellow at the Max Planck Institute for the Study of Societies), the conference explored two themes (1) socially contested boundaries between legality and illegality and (2) blurring boundaries between legal and illegal actions. The keynote speakers of the conference were Keith Hart (London School of Economics, UA), whose lecture opened the first day, and Peter Reuter (Maryland University, USA), whose speech closed the conference.Organizers invited scholars from different disciplines including economic sociology, economic anthropology, legal studies, and criminology. Invited speakers included Kirsten Endres (the Max Planck Institute for Social Anthropology), Matías Dewey (the Max Planck Institute for the Study of Societies), Philippe Steiner (Paris-Sorbonne University), Nina Engwicht (the Max Planck Institute for the Study of Societies), Simon Mackenzie (Glasgow University), Annette Hübschle (the Max Planck Institute for the Study of Societies), Renate Mayntz (the Max Planck Institute for the Study of Societies), Vadim Radaev (Higher School of Economics), Paolo Campana (Oxford University), Boris Samuel (Sciences Po), Michael Levi (Cardiff University), and Ronen Palan (City University of London).